Instalación y configuración del chan mobile en asterisk y su conexión a la red gsm - Jijón Albán, Jason (2009)
This work involves the implementation of a small Asterisk based PBX capable of accessing GSM network using Chan Mobile module what allows using cell phones from the IP telephony network connected to the Asterisk server that require establish communication to GSM mobile device. With the implementation of this project we efficiently administrate the for business use by considering: the acquisition hardware cost, that calling between cells of a same mobile operator is always cheaper, the control over the call’s length, hierarchy of access to output channels by us using text messages (SMS) as a additional alternative to calls due to they are cheaper and their impact on the server is less.